Menarche and menopause in height - Coyotupa Vega, Juan (2015)
We have evaluated the age of menarche and menopause in the Andean High Altitude. The study was done in III women age ranged from 38 to 62 years old, 49 were from high land living at 4340 m altitude and 62 women from sea level. In women from High Altitude the age of menarche was 14,6 ± 0,2, the age of menopause was 45,3 ± 0,7 and the reproductive live was 30,7 ± 0,9. In women from sea level the age of menarche was 12,6 ± 0,2, the age of menopause was 48,2 ± 0,7 and the reproductive live was 35,4 ± 0,9. These results indicated that in High Altitude the age of menarche occurred 2 years later, the age of menopause was 2,9 years earlier and the reproductive live was 4,8 years shorter than women living at sea level. The pregnancy rate at High Altitude was 7,3 ± 0,5 and at sea level was 2,8 ± 0,4 indicating that the High Altitude does not interfere with the normal reproduction.